2019
DOI: 10.1002/mp.13366
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of linear least‐squares, nonlinear least‐squares, and Patlak graphical method for regional and local quantitative tracer kinetic modeling in cerebral dynamic 18F‐FDG PET

Abstract: Purpose Dynamic 18F‐FDG PET allows quantitative estimation of cerebral glucose metabolism both at the regional and local (voxel) level. Although sensitive to noise and highly computationally expensive, nonlinear least‐squares (NLS) optimization stands as the reference approach for the estimation of the kinetic model parameters. Nevertheless, faster techniques, including linear least‐squares (LLS) and Patlak graphical method, have been proposed to deal with high resolution noisy data, representing a more adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In the few cases where radio-metabolites overlapped with the parent tracer because of similar polarity and hence strength of adhesion to the silica media, the parent tracer peak could be adequately resolved by the curve fitting procedure discussed in §2.6. Taken the above results together, our method of combining TLC and the Beaver proprietary beta particle detector has the analyte resolution and sensitivity for blood metabolite determination for both [18 F]FAZA and [ 18 F]FEPPA in individual large (pig) or small (rodents) animals. Nevertheless, by comparing the [ 18 F]FEPPA dose used in our pig studies (13−27 MBq/kg) to the published patient dose (2.5 − 6.2 MBq/kg (22-25)) the sensitivity of the detector has to be increased by at least 5 times for the method to be used for blood metabolite determination in individual patients.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…In the few cases where radio-metabolites overlapped with the parent tracer because of similar polarity and hence strength of adhesion to the silica media, the parent tracer peak could be adequately resolved by the curve fitting procedure discussed in §2.6. Taken the above results together, our method of combining TLC and the Beaver proprietary beta particle detector has the analyte resolution and sensitivity for blood metabolite determination for both [18 F]FAZA and [ 18 F]FEPPA in individual large (pig) or small (rodents) animals. Nevertheless, by comparing the [ 18 F]FEPPA dose used in our pig studies (13−27 MBq/kg) to the published patient dose (2.5 − 6.2 MBq/kg (22-25)) the sensitivity of the detector has to be increased by at least 5 times for the method to be used for blood metabolite determination in individual patients.…”
mentioning
confidence: 73%
“…Significant inter-subject and intra-subject variability in radiometabolites production could be observed with both tracers. For [ 18 F]FEPPA, 50% of plasma activity was from radiometabolites as early as 5 min post injection while for [ 18 F]FAZA, significant metabolites did not appear until 50 min post. Simulation study investigating the effect of radio-metabolite in the estimation of kinetic parameters indicated that 32-400% parameter error can result without radio-metabolites correction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Without this correction, the AIF will be overestimated leading to errors in the kinetic analysis of dynamic PET. Although we used two specific tracers, [ 18 Figure A2, the percentage bias of the same parameters as in Table 3 -1 , 2 , 3 , 4 , , , and , as estimated by AIF m and AIF c , differs widely among the different scale…”
Section: Resultsmentioning
confidence: 99%